OPTIMIZATION OF ANNEALING TEMPERATURE FOR COI GENE AMPLIFICATION ON EXTRIMOPHIL FISH USING PCR - Kurniawan, Ardiansyah; Anjani, Tiara Puspa; Lestari, Eva; Safitri, Alya M; Kurniawan, Andri; Syarif, Ahmad Fahrul; Apriyani, Rina; S, Merin; Ichsan, Muhamad; Almagribi, Siti P N I K (Jurusan Akuakultur, Universitas Bangka Belitung, 2022)
Extremophilic fish require genetic characterization to determine the identity of their species, their kinship, and the potential for genetic variation due to extreme environmental adaptation. DNA barcoding using Fish-F2 and Fish-R2 primers at an annealing temperature of 52oC for 15 seconds showed qualitative failure results in most fish species. For this reason, optimizing the annealing temperature in the PCR process is necessary to obtain DNA bands that correlate with successful identification. Fish samples were obtained from Ruai Silip, Bangka Island, Membalong, Belitung Island, and Way Kanan, Lampung, Sumatra Island. The annealing temperature optimization was set at 50, 50.4, 51.1, 52.3, 53.7, 54.8, 55.5, and 56°C. Five species of extremophile fish were tested, namely Brevibora sp, Barbodes binotatus, Rasbora bankanensis, Anabas testudineus, and Aplocheilus panchax. Extremophile fish showed differences in the appearance of DNA bands in PCR with different annealing temperatures. Brevibora sp showed a visualization of DNA bands at 54.8°C, Barbodes binotatus at 53.7, 54.8, 55.5, and 56°C, Anabas testudineus at 50 and 50.4°C, and Aplocheilus panchax produced clearly visible band on annealing temperatures.